Comportamento físico de um latossolo sob integração lavoura - pecuária - Kunz, Marcelo (2009)
Soil compaction under traffic of animals has become an increasingly significant problem in soils used for crop-livestock integration. The objective of this study was to determine the effect of integration crop-livestock and different soil management systems on their attributes water and mechanical and relate them to the development and productivity of soybean. The specific objectives were: to investigate the effect of the absence of animal trampling on the water and mechanical attributes of soil and growth of soybean; to evaluate susceptibility to soil compaction by the parameters of the compressibility of the soil; determine the relationship of permeability to air with the tension of the water and soil pore space; evaluate the relationship between plant growth and water content; evaluate the residual effect of chiseling. The experiment was installed in 2007, in a commercial agricultural area in the municipality of Ibirubá (RS). The soil of the place is classified as Oxisol. Bulk density (Ds), macroporosity (Ma), microporosity (Mi) total porosity (Pt) resistance to penetration (RP) and soil moisture (θ), emergence and plant height, root growth and yield of soybean were evaluated. The experimental design was randomized blocks with three replications. The treatments were: tillage without grazing (SDS / P), tillage with grazing (SDC / P) and chiseling (Esc). The Ds, Mi, Ma, En, CRA and Ka were determined in soil samples collected with the structure preserved in layers: 0-0,07; 0,07- 0,15 e 0,20-0,30 m in three periods: before grazing (August 2007), post-grazing (December 2007) and post-grazing (October 2008). The soil compression curve in balanced sample was determined in tension of 0.03 MPa in the first two layers above. The results indicated that the chiseling sporadic in soils under crop-livestock integration without tillage provides soil hydro-physical conditions less favorable for the development of plants. The preparation with chisel negatively affected grain yield of soybean. The soil whit chiseling had its proprieties changed by the treading of animals, reducing the residual effect of it. The absence of animals did not promote significant changes in Ds, Mi, Ma and Pt managed under the soil tillage. The chiseling decreased soil moisture compared to other treatments. The PR showed a direct relationship with soil moisture, for below 20% obtained values above 2 MPa for RP were. In SD/CP, the root system showed deviation of growth in depth, especially in the 0-0,07 m layer. The deviation unobserved in SD/SP and Esc. The same behavior was not observed in SD/SP and Esc. in years with water deficit. The plant height in SD/SP was higher than in other treatments and the lowest grain yield was obtained in Esc. Highest Ka was observed in lower potential matric and the surface layer of soil, where there is greater presence of macroporosity, with reduction in depth. A direct relationship between the soil Ka and εa was observed. The pressure applied by the traffic of animals increased the values of σp in the surface layer. With chiseling of the soil, the surface layer had less ability to support loads and greater susceptibility to compaction.